Development of a blended MOOC implementation model for English language learning: An interpretive structural modeling approach - Anh Tuan Pham; Muhammad Ridhuan Tony Lim Abdullah (PLoS ONE, 2026)
The integration of Massive Open Online Courses (MOOCs) into traditional English language education has created new opportunities for scalable, flexible, and inclusive learning. However, existing studies on MOOCs and blended learning remain largely descriptive and lack a structured framework that prioritizes key implementation elements for effective integration into formal education. This study develops a structured implementation model for blended MOOCs (bMOOCs) tailored to undergraduate English as a Foreign Language (EFL) instruction. This gap is particularly evident in specific contexts such as Vietnam, where institutional conditions, technological readiness, and learner characteristics significantly influence implementation effectiveness. Using the Interpretive Structural Modelling (ISM), the research identifies and validates 20 key sub-indicators grouped into three interconnected phases: planning, implementation, and evaluation. The model emphasizes the importance of analyzing learners’ backgrounds and motivations, setting clear learning objectives, and selecting appropriate materials and technologies. During implementation, the focus shifts to effective instructional strategies, learner participation, and technical support. The evaluation phase prioritizes formative assessment and timely feedback to promote continuous improvement and engagement. This learner-centered approach addresses common challenges in blended learning environments. The model offers practical guidance for stakeholders in EFL education, such as administrators, educators, and curriculum developers, seeking to enhance English language education through blended MOOCs. Practical implications for the implementation of blended MOOCs in EFL instruction are also addressed to enhance the quality of English language instruction in the digital age.